An Informational Analysis of Reaction Times to Different Intensities of Light - Fulgosi, Ante (Array, 2003)
Twelve circular areas of the same size (50) differing in light intensities from 1 lux to 1000 luxes in equal logarithmic steps were presented to 5 subjects 80 times each in a random order. Informational value of this set of stimuli was 3.585 bits. Reaction time (RT) to each stimulus presentation was registered in milliseconds. It was found that the registered RT to different light intensities were almost completely overlapped and informational analyses have shown that they are composed almost completely from equivocation and ambiguity and contain only a small amount of information (0.63 bits), not enough to discriminate even two levels of light intensities. It was concluded that RT represents a much poorer informational channel than subjective estimates (for which informational analyses have shown to contain about 3 bits of information).